The Effects Of Topical Antiglaucoma On The Conjunctival Cell Profile - Tajudin, Liza Sharmini Ahmad (2001)
Topical antiglaucoma drugs were implicated to cause subclinical chronic inflammation , which was believed to be responsible in inducing excessive scarring of the filtering bleb. Our aim is to investigate the effects of topical antiglaucoma drugs on conjunctival cell profile when compared to eye not expose to the drugs. The effects of duration of treatment, type of drugs and number of topical anti glaucoma drugs on conjunctival cell profile were also evaluated. Histological